TELAAH KRITIS FATWA MAJELIS ULAMA INDONESIA (MUI) TERHADAP PRODUK SANDANG - Afifatul Munawiroh; M. Khoirul Hadi al- Asy'ari (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
This research based on Islamic Economisation in Indonesian: a Critical review of the editcts of the Majelis Ulama Indonesia (MUI) on Clothing products and their effects on the migration of life style discourse in Indonesian. In this paper there are three important questions. First, how is the history of the emergence of legal labeling in Majelis Ulama Indonesia? Second, how to develop products that are labeled halal labeling on clothing from Majelis Ulama Indonesia? Third, How the impact of halal labeling on clothing from Majelis Ulama Indonesia? With the approach of the Phemenology to expalain develop produvts that are labeled halal lebeling on clothing from Majelis Ulama Indonesia and explain the impact of halal labeling on clothing from Majelis Ulama Indonesia. And then, the history of the emergence of legal labeling in Majelis Ulama Indonesia expalain in the analysis content. The results of this study are first, to know the history of the emergence of legal labeling in Majelis Ulama Indonesia second, to know develop products that are labeled halal labeling on clothing from Majelis Ulama Indonesia third, to know the impact of halal labeling on clothing from Majelis Ulama Indonesia.